(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Osteoporosis is a now becoming the major public health problem in Indian women. The probable causative factors include disturbed lifestyle affecting the diet of an individual’s viz. low calcium intakes with extensive prevalence of vitamin D deficiency, increasing longevity, early menopause, genetic predisposition, lack of diagnostic facilities, and poor knowledge of bone health have contributed toward the high prevalence of osteoporosis. . The recent researches also suggest that development of Osteoporosis is more in women than men. This is due to the fact that women have low peak bone mass and small bones than men. They also lose bone mineral density more rapidly than men in middle age because of the dramatic reduction in estrogen levels that occur with menopause. The study was aimed to analyze the prevalence of osteoporosis among women hence relevant data was collected by analyzing different research papers which were published in scholarly journals with the help of scientific electronic database viz. Pubmed, Google scholar etc.